Potential false positive active extra pulmonary tuberculosis lesions on FDG PET/CT imaging in malignancy. - Jalil, Abdul Jalil; Rossetti, Claudio; Abdul Rahim, Noraini; Rashmizal, Hairil (Dicle University Medical School, 2010)
Objectives: Integrated fusion imaging modality Positron Emission Tomography Computed Tomography (PET/CT)using 18Fluorine-Fluoro Deoxy Glucose (18F-FDG) iscommonly utilized in imaging oncology. We expand therole of this imaging modality in our study to demonstratethe appearance of active extra pulmonary tuberculosis(TB) lesions.